Respuesta :

Space

Answer:

(f * g)(x) = -18x² + 63x - 55

General Formulas and Concepts:

Algebra

  • Expand by FOIL (First Outside Inside Last)
  • Terms/Coefficients/Degrees

Step-by-step explanation:

Step 1: Define

f(x) = -6x + 11

g(x) = 3x - 5

(f * g)(x) is f(x) · g(x)

Step 2: Find

  1. Substitute:                              (f * g)(x) = (-6x + 11)(3x - 5)
  2. Expand [FOIL]:                        (f * g)(x) = -18x² + 30x + 33x - 55
  3. Combine like terms:              (f * g)(x) = -18x² + 63x - 55